Hepatoprotective Efficacy of Residual Aqueous Fraction of Bombax costatum Pellegr. Et Vuillet (Bombacacae) Stem Bark Against Carbon Tetrachloride Induced Acute Liver Toxicity in Mice - Nuhu Mohammed; Umar Abdullahi; Ahmadu Saleh; Umar Bala Ningi; Muhammad Rabiu Hamza (West African Journal of Allied Health Sciences, 2026)
Introduction: Hepatic disease still remains a major public health problem due to vulnerability of the liver to a variety of metabolic, circulatory, neoplastic, xenobiotic and microbial insults. Liver injury is accompanied with derangement of vital body functions, hence the need to search for efficacious hepatoprotective agents with minimal side effect. This study aimed to evaluate the hepatoprotective efficacy of aqueous fraction of B. costatum stem bark (AFB) against carbon tetrachloride (CCl4) induced acute liver toxicity in mice. Methods: Swiss albino mice were divided in to groups I-VI with each group containing 6 mice. Group I and II served as normal and toxic control groups respectively. Group III mice were pre-treated with silymarin (100 mg/kg) daily for 7 days. Mice in groups IV-VI were pre-treated with 125, 250 and 500 mg/kg of AFB daily for 7 days respectively. Acute hepatotoxicity was induced via intraperitoneal administration of 1 ml/kg of CCl4 to mice in groups II-VI on the 8th day of the study. Effect of treatments on serum alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), total bilirubin (TB) as well as liver architecture were evaluated. Results: Pre-treatment of the mice with AFB at 250 mg/kg and 500 mg/kg significantly (p